PENGARUH REPUTASI UNDERWRITER, PERSENTASE SAHAM YANG DITAWARKAN KE PUBLIK, DAN PENGGUNAAN DANA IPO UNTUK INVESTASI TERHADAP TINGKAT UNDERPRICING SAHAM SYARIAH PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2013-2016 - Nur Afni Yunita; Muftia Chairunnisa (Jurnal Akuntansi dan Keuangan, 2017)
This study aims to examine the influence of underwriter reputation, the percentage of shares offered to the public and the use of IPO funds for investment to the level of underpricing of Islamic shares in companies conducting IPOs in 2013-2016. The sampling technique used is a purposive sampling in which the selection of samples based on certain criteria, so that the sample obtained in this study are 33 companies from a population of 342 companies. The dependent variable in this study is underpricing, while the independent variable is the underwriter's reputation, the percentage of shares offered to the public, and the use of IPO funds for investment. This study uses multiple regression analysis with hypothesis testing using SPSS 16 for Windows. The results show that the Underwriter reputation does not significantly influence the underpricing of sharia shares. The percentage of shares offered to the public does not significantly influence the underpricing of Islamic shares and the use of IPO funds for investment does not significantly influence the underpricing of Islamic shares.